Weekly Subject Index to Current Contents® - Gabfibld, E. (Methods of Information in Medicine, 1974)
Four of the six editions of Current Contents® (CC®) now carry a title-word index called the Weelcly Subject Index (WSI). The WSI provides an adjunct to Current Contents® which permits the editions to grow with the literature growth and still allows for rapid scanning and identification of relevant articles by the reader. The T’FSI alphabetically lists every significant word from every title announced in a given CC® issue. The result is a new access tool for CC® which makes weeldy searches for relevant information even faster, easier and more productive. The WSI also reinforces CC’s capability for filling the time gaps between regular issues of retrospective indexes.
Keywords: Current Contents; Weeldy Subject Index; Rapid Scamiing; Current Awareness; Title Word Indexes